Measurements and Processing of Signals used in a Cab Signaling System - Augutis, V.; Gailius, D.; Misevicius, R.; Juraska, M. (Elektronika ir Elektrotechnika, 2012)
Automatic cab signaling system used in Lithuanian Railways is uninterruptible signaling system used to transmit the information about an allowable train speed to a cab driver. The performance of this system can be disturbed by various sources of disturbances. One of the main sources is a magnetization of rails. So far there were no other methods to evaluate disturbances that can cause signaling system errors than going by train and monitoring traffic-light signals in a cab. Therefore a system to record signaling system signals was created and a method to process the signals was proposed. The method can be used to make a signal processing and decoding of the previously decoded signals. Furthermore, the proposed algorithm uses slightly different method of signal processing and is potentially more immune to disturbances caused by the rail magnetization. The proposed algorithm was used to process the real signaling system signals. The signals were recorded on a route by going on an electric train. The main results of processing and potential places of disturbances have been shown. The advantage of the proposed algorithm over the currently used one need to be investigated in further research. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2800